2019
DOI: 10.3389/fmicb.2019.02885
|View full text |Cite
|
Sign up to set email alerts
|

The Host Heat Shock Protein MRJ/DNAJB6 Modulates Virus Infection

Abstract: A variety of pathogens take advantage of cellular heat shock proteins (HSPs) to complete their life cycle and exert pathogenic effects. MRJ (DNAJB6), a member of the heat shock protein 40 family, acts as a molecular chaperone for a wide range of cellular processes. MRJ mutations are linked to human diseases, such as muscular dystrophy and neurodegenerative diseases. There are two MRJ isoforms generated by alternative use of terminal exons, which differ in their C-terminus. This mini-review summarizes how these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 92 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…In addition, heat shock proteins (HSPs) were upregulated in B. tabaci (MED) following TYLCV acquisition [ 48 ]. HSPs are reported to play a role in cell entry, replication and particle assembly, and movement in several animal viruses [ 135 ]. HSPs also are molecular chaperones responsible for cellular defense mechanisms against deleterious effects such as protein misfolding, degradation, and insoluble aggregation [ 136 ].…”
Section: Plant-virus-induced Responses In Vectorsmentioning
confidence: 99%
“…In addition, heat shock proteins (HSPs) were upregulated in B. tabaci (MED) following TYLCV acquisition [ 48 ]. HSPs are reported to play a role in cell entry, replication and particle assembly, and movement in several animal viruses [ 135 ]. HSPs also are molecular chaperones responsible for cellular defense mechanisms against deleterious effects such as protein misfolding, degradation, and insoluble aggregation [ 136 ].…”
Section: Plant-virus-induced Responses In Vectorsmentioning
confidence: 99%
“…Direct interaction in the DNAJB6 and prion protein during viral infection has been shown to favor nuclear localization of the HIV-1 pre integration complex. In addition, the delivery of primase-UL70 into cell nuclei through DNAJB6 may promote the synthesis of viral DNA during HCMV infection [ 40 ]. Although not all miRNA in the two circRNA networks selected in this study have binding with mRNA, they may be involved in CVB5 infection because they were the target molecules of circRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Heat-shock proteins function as molecular chaperones to maintain proteostasis [113]. A number of viruses modulate the cellular heat-shock response or take advantage of cellular heat-shock proteins to overcome host environmental challenges and complete their life cycle [114,115]. An early study revealed that the human heat-shock protein DNAJB6 (also termed MRJ) is critical for nuclear import of the HIV-2 preintegration complex via its interaction with viral Vpx protein [116].…”
Section: The Heat-shock Protein Mrjmentioning
confidence: 99%
“…An early study revealed that the human heat-shock protein DNAJB6 (also termed MRJ) is critical for nuclear import of the HIV-2 preintegration complex via its interaction with viral Vpx protein [116]. Notably, MRJ has two splice isoforms that exert different effects on viral infection [115]. Isoform switching from the C-terminally truncated MRJ-S to full-length MRJ-L occurs during monocyte differentiation into macrophages, which are target cells for HIV [117].…”
Section: The Heat-shock Protein Mrjmentioning
confidence: 99%